2018
DOI: 10.1017/s1368980018002677
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and trends in the intake distribution of manufactured and homemade sugar-sweetened beverages in pre-tax Mexico, 1999–2012

Abstract: Objective: To describe trends across the intake distribution of total, manufactured and homemade sugar-sweetened beverages (SSBs) from 1999 to 2012, focusing on high SSBs consumers and on changes by socioeconomic status subgroups. Design: We analyzed data from one 24-hour dietary recall from two nationally representative surveys. Quantile regression models at the 50th, 75th and 90th percentiles of energy intake distribution of SSBs were used. Setting: 1999 Mexican National Nutrition Survey and 2012 Mexican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Studies have shown that the percentage of children and adolescents who consume soft drinks in China increased from 73.58% to 90.49% from 2004-2011, and the average weekly consumption increased to 1.5 L [42]. In Mexico, the energy intake of soft drinks increased significantly from 1999 to 2012, contributing to 9.8% of the total daily energy intake by 2012 [43]. An excess consumption of soft drinks can induce obesity, dental caries, and shortened sleep periods, which can lead to severe damage to the body's organs and increase the risk of diabetes, hypertension, and all-cause mortality [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the percentage of children and adolescents who consume soft drinks in China increased from 73.58% to 90.49% from 2004-2011, and the average weekly consumption increased to 1.5 L [42]. In Mexico, the energy intake of soft drinks increased significantly from 1999 to 2012, contributing to 9.8% of the total daily energy intake by 2012 [43]. An excess consumption of soft drinks can induce obesity, dental caries, and shortened sleep periods, which can lead to severe damage to the body's organs and increase the risk of diabetes, hypertension, and all-cause mortality [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…SSB was defined SSB as any liquids that are sweetened with various forms of added sugars [ 1 ]. Consistent with recent evidence from LAC [ 12 , 16 ], SSB were divided into two categories: homemade, which included homemade beverages with added sugar (e.g., tea, coffee, fruit juices), and ready-to-drink SSB, which included beverages with added sugar purchased ready to drink (e.g., soda, energy drinks, sweetened water, nectar). If ready-to-drink SSB were mixed with alcoholic beverages (e.g., coke mixed with vodka), we only considered the amount of the SSB (i.e., the amount of the alcoholic beverage was removed).…”
Section: Methodsmentioning
confidence: 99%
“…Characteristics of the 21 studies (Holstein et al, 2020; Kelly et al, 2019; Pinto et al, 2019; Batis et al, 2016; Makkes et al, 2011; Clifton et al, 2011; Miller et al, 2020; Mathur et al, 2020; Rombaldi et al, 2011; Niven et al, 2014; Arcan et al, 2014; Rouche et al, 2019; Vereecken et al, 2005; Sayegh et al, 2002; Schneider et al, 2020; Olmedo et al, 2018; Han and Powell 2013; Bernsdorf et al, 2016; French et al, 2013; McNeill et al, 2017; Aburto et al, 2018) included in the systematic review are represented in Table 2. Of these, 13 were cross-sectional (Kelly et al, 2019; Pinto et al, 2019; Batis et al, 2016; Makkes et al, 2011, Clifton et al, 2011; Miller et al, 2020; Mathur et al, 2020; Rombaldi et al, 2011; Niven et al, 2014; Arcan et al, 2014; Rouche, et al 2019; Vereecken et al, 2005) two were longitudinal (Olmedo et al, 2018; Han et al, 2013) and trend analysis or panel data was available for the remaining six studies, with the majority of them being National surveys reported from developed countries (Holstein et al, 2020; Han et al, 2013; Bernsdorf et al, 2016; French et al, 2013; McNeill et al, 2017; Aburto et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies mentioned below were excluded from meta-analysis due to wide variation in the classification of SES, or there was no clarity on the type of SSB consumed. Aburto et al, (2018) and Niven et al, (2014) classified SES into tertiles and quintiles, respectively, and Clifton et al (2011) did not use SES classification. Makkes et al (2011) and, Han and Powell (2013), Arcan et al, (2014) Sayegh et al, (2002) classified SES into only two categories (low and medium) and (low and high), respectively.…”
Section: Resultsmentioning
confidence: 99%